2019
DOI: 10.1093/ecco-jcc/jjz095
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab Treatment in Extra-Intestinal Manifestations in Inflammatory Bowel Disease: A Systematic Review

Abstract: Background and Aims We aimed to summarize existing data on the effectiveness of vedolizumab in extra-intestinal manifestations [EIMs] in inflammatory bowel disease [IBD]. Methods We conducted a systematic literature search in PubMed and the Cochrane Library, up to October 2018. Interventional and non-interventional studies as well as case-series studying vedolizumab and EIMs in adult patients with IBD were considered eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…Chateau et al reported two factors as paradoxical manifestations and extra-intestinal expression of MAdCAM-1. 11 PG lesions may be treated with systemic corticosteroids and anti-TNF-α agents. Other options reported to be effective for treating PG lesions include corticosteroids, dapsone, minocycline, methotrexate, cyclosporine, mycophenolate mofetil, and intravenous immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…Chateau et al reported two factors as paradoxical manifestations and extra-intestinal expression of MAdCAM-1. 11 PG lesions may be treated with systemic corticosteroids and anti-TNF-α agents. Other options reported to be effective for treating PG lesions include corticosteroids, dapsone, minocycline, methotrexate, cyclosporine, mycophenolate mofetil, and intravenous immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…94 In a systematic review, vedolizumab was suggested to reduce the incidence of new EIMs but also be effective in the treatment of preexisting EIMs (particularly PSC, rheumatic and cutaneous manifestations). 95 Data on other biologicals are limited. Ustekinumab is a fully human IgG1 kappa monoclonal antibody that blocks the IL-12/23 p40 subunit.…”
Section: Biologics and Probiotics For Eimsmentioning
confidence: 99%
“…According to these results, vedolizumab has no direct therapeutic effect on cutaneous EIMs and can play a role in EIM management by treating disease activity in EIMs that parallels IBD [ 94 ]. In a systematic review, vedolizumab was suggested to reduce the incidence of new EIMs but also be effective in the treatment of preexisting EIMs (particularly PSC, rheumatic and cutaneous manifestations) [ 95 ].…”
Section: Treatment For Eims Including Biologicsmentioning
confidence: 99%
“…the published work, vedolizumab does not improve pre-existing extraintestinal manifestations of IBD. 3 Indeed, although his gastrointestinal symptoms improved significantly, the patient was still not able to decrease the prednisone to less than 25 mg/day due to persistently active PG. When the patient was first referred for dermatological consultation, he had several painful ulcers on both lower and upper limbs, axillary area, chest, back and face; the clinicopathological features of these lesions confirmed the diagnosis of PG, as reported by Su et al, 4 including the two major criteria and more than two minor ones ( Fig.…”
mentioning
confidence: 95%